Monitoring pain during use of virtual reality in debridement procedures of vascular wounds in outpatient care settings - Przybek-Mita, Joanna; Bazaliński, Dariusz; Surmacz, Anna; Kołodziej, Anna; Bryła, Julia (Frontiers in Medicine, 2025)
IntroductionVirtual Reality (VR) is an advanced technological system which, besides its use in entertainment and education, has been permanently introduced over the past quarter-century into physical and psychiatric rehabilitation as well as medicine. Its effectiveness has been demonstrated in pain management during medical and rehabilitation procedures in burn patients, alleviation of cancer pain, and reduction of labor pain. VR is increasingly used during routine medical procedures in children, such as blood sampling, intravenous cannulation, and vaccination, and holds promise for chronic pain management.ObjectiveThe aim of this study was to assess pain during the treatment of hard-to-heal wounds of vascular origin using VR as an adjunct non-pharmacological pain therapy.Materials and methodsAn observational study was conducted in a chronic wound care clinic involving 100 patients. The mean age was 68.02 ± 10.0 years. All participants had hard-to-heal wounds of vascular origin. The mean wound duration was 7.16 ± 5.08 months, with an average wound area of 39.18 ± 71.83 cm2 (range 2 cm2 to 625 cm2). Patients were randomly assigned to a group distracted with VR goggles and a control group receiving standard care without VR. Pain intensity was assessed using the Numeric Rating Scale (NRS) at three time points, and the McGill Pain Questionnaire (MPQ) before the procedure, during wound debridement, and 10 min after completion.ResultsStatistically significant differences were observed in pain assessment before and during wound debridement (p < 0.05). In the VR group, higher pain scores were recorded before wound care compared to the control group. Ten minutes before wound debridement, the mean pain intensity in the VR group was 2.60 ± 1.63, higher than 2.0 ± 1.53 in the control group. During wound debridement, pain intensity was higher in the control group (4.94 ± 1.53) compared to the VR group (4.32 ± 2.17). Pain intensity 10 min after debridement was similar in both groups: control (2.24 ± 1.41) and VR (2.36 ± 1.71). These findings support the hypothesis that VR goggles reduce pain intensity. No statistically significant differences in NRS pain scores were found between patients with different wound types in either group (p > 0.05). Variables such as wound duration and wound size influenced pain levels 10 min before wound care. No association was found between sex and pain intensity (p > 0.005).ConclusionIncreased pain during procedures involving manipulation of damaged tissues and wound debridement is a common phenomenon. This study confirmed that the use of VR goggles reduces perceived pain levels. The assessment of pain experience and intensity varies depending on the assessment tools used; therefore, a combined quantitative and qualitative evaluation is recommended to accurately determine the usefulness of innovative tools in clinical practice.